Structural and External Barriers to Pakistan’s Economic Growth: Pathways to Sustainable Development - Naveed Ali; Olivier Karl Butzbach; Habib Ali Katohar; Hassan Imran Afridi (World)
Pakistan’s economic growth has been hindered by various internal and external factors since its independence in 1947. This study aims to identify the root causes of these issues and provide a comprehensive understanding of the country’s economic situation. Internally, inefficient bureaucracy, corruption, inadequate support for small and medium enterprises (SMEs), labor market rigidity, tax evasion, and regional inequalities have impeded development. External factors such as political instability, terrorism, weak governance, foreign policy challenges, and insufficient infrastructure have discouraged investment and disrupted economic activities. Pakistan’s reliance on low-tech exports has also led to a loss of competitiveness in international trade. To revitalize the economy, the study suggests reforms in governance, bureaucracy, and infrastructure, with a focus on supporting SMEs, reducing corruption, and attracting investment. The adoption of circular economy (CE) practices, particularly through the use of recycled materials, is proposed as a viable pathway to enhance economic resilience and environmental sustainability. The study highlights the potential for integrating CE strategies, drawing from successful global practices, to address Pakistan’s economic and environmental challenges. However, the reliance on historical data and linear econometric models may not fully capture the evolving economic dynamics, necessitating further research incorporating real-time data and sector-specific approaches. Despite these limitations, the study provides actionable insights for policymakers, offering a framework for Pakistan and other developing economies to achieve sustainable growth.